Titanium dioxide nanotubes in a hydrogen peroxide-based bleaching agent: physicochemical properties and effectiveness of dental bleaching under the influence of a poliwave led light activation - Antunes, Edina Veloso Gonçalves; Basting, Rosanna Tarkany; do Amaral, Flávia Lucisano Botelho; França, Fabiana Mantovani Gomes; Turssi, Cecilia Pedroso; Kantovitz, Kamila Rosamilia; Bronze-Uhle, Erika Soares [UNESP]; Filho, Paulo Noronha Lisboa [UNESP]; Basting, Roberta Tarkany (Springer Nature, 2023)
Objectives: The effects of different concentrations of titanium dioxide (TiO2) into 40% hydrogen peroxide (HP) were evaluated as regards the effectiveness of dental color change either associated with activation by polywave LED light or not. Materials and methods: TiO2 (0, 1, 5, or 10%) was incorporated into HP to be applied during in-office bleaching (3 sessions/40 min each). Polywave LED light (Valo Corded/Ultradent) was applied or not in activation cycles of 15 s (total time of 2 min). The color of 80 third molars separated into groups according to TiO2 concentration and light activation (n = 10) was evaluated at baseline and at time intervals after the 1st, 2nd, and 3rd bleaching sessions. Results: WID value was significantly higher when using HP with 5% TiO2 in the 2nd session than the values in the other groups (p < 0.05). After the 2nd and 3rd sessions, the ΔEab value was significantly higher when activated with light (p < 0.05) for all agents containing TiO2 or not. Zeta potential and pH of the agents were not modified by incorporating TiO2 at the different concentrations. Conclusions: The 5% TiO2 in the bleaching agent could enhance tooth bleaching, even without light application. Association with polywave LED light potentiated the color change, irrespective of the presence of TiO2 in the bleaching gel. Clinical significance: HP with 5% TiO2 could lead to a greater tooth bleaching response in the 2nd clinical session, as well as the polywave light can enhance color change.
Keywords: Dental bleaching; Hydrogen peroxide; Poliwave LED light; Titanium dioxide